The effectiveness of nudging interventions to promote healthy eating choices: A systematic review and an intervention among Italian university students. (1st January 2022) - Cesareo, Massimo; Sorgente, Angela; Labra, Massimo; Palestini, Paola; Sarcinelli, Beatrice; Rossetti, Massimiliano; Lanz, Margherita; Moderato, Paolo
Abstract: Nudges are changes in choice architecture (i.e., the environment in which people make decisions) aiming to steer a person's decision to a particular choice, without restricting alternative options or changing financial incentives. These strategies have been extensively used to promote healthy eating, above all among youths, whose behaviors can still be easily shaped compared to older people's. The current paper describes two studies aiming to investigate the effectiveness of nudging interventions in promoting healthy eating among university students. The first study consisted of a systematic review mapping all the published studies which describe the effectiveness of this kind of intervention worldwide. Twelve eligible records were selected after a search of three different databases. Information about the publication of the record, the adopted research methods and the described intervention was retrieved from each selected record. Based on this review's results, a new nudging intervention was developed to promote healthy food choice among Italian university students. The intervention aimed to modify students' choice for each of the Italian meal courses: first course (pasta, rice or soup), second course (meat, fish, cheese or cured meat), side dish, bread, and fruit. An Italian university cafeteria was observed in two phases: a pre-intervention phase (baseline) and a post-intervention phase (nudging strategies were implemented in the cafeteria's architecture). The applied nudging intervention was effective in promoting healthy choices in relation to the second course, the side dish, and the bread, but it did not significantly affect choices related to the first course or the fruit. Implications of these results and suggestions for future interventions are discussed.